2022
DOI: 10.1109/tii.2021.3096947
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Stage Control Strategy for a Flying Capacitor Converter Based on Model Predictive and Linear Controllers

Abstract: This work proposes a novel dual-stage control strategy for a Flying Capacitor converter. During transients, the proposed control scheme applies Finite-Control-Set Model Predictive Control (FCS-MPC) to drive the system close to the desired reference, including all the known non-linearities of the system in the converter model. When the converter state is in a neighborhood of the reference, the dual-stage controller switches to a PWM-based linear controller with an integral action. In this case, the linear contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Switching between controllers is a challenging task that causes undesired bumps and oscillations [61]. An HC approach is utilized in [127] to commutate between model predictive control and a linear PI controller to control a flying capacitor VSI. An average-current ripple-based HC scheme is proposed, along with an artificial neural network-based method, in [61] for PMSM drive systems.…”
Section: Hysteresis Controlmentioning
confidence: 99%
“…Switching between controllers is a challenging task that causes undesired bumps and oscillations [61]. An HC approach is utilized in [127] to commutate between model predictive control and a linear PI controller to control a flying capacitor VSI. An average-current ripple-based HC scheme is proposed, along with an artificial neural network-based method, in [61] for PMSM drive systems.…”
Section: Hysteresis Controlmentioning
confidence: 99%
“…As for the existing MPC strategies in FCC converters, the majority of them are based on FCS-MPC [38,[58][59][60][61][62][63][64], with practically no studies being reported in the literature using CCS-MPC for this type of converter.…”
Section: Mpc In Converter Topologies Typically Used In Sstsmentioning
confidence: 99%
“…For planar motors, most control methods have been developed for high-precision point-to-point motion; and only several control methods have been exploited for high-precision trajectory tracking motion, such as the optimal proportional-integral-derivative (PID) control [6], data-driven model-free optimal control [7], hybrid control combining of adaptive robust control and iterative learning control [8], and model predictive control (MPC) [9]. It is found that MPC is an attractive and promising optimal control method due to its merits, such as simplicity in design and implementation, fast dynamic response, broad applicability, and strong ability to multiobjective constrained optimisation [10][11][12]. Currently, MPC has gained increasing attention and application in fast-varying motor systems [13][14][15] and has been emerging and applied in planar motors [1,9].…”
Section: Introductionmentioning
confidence: 99%